2011
DOI: 10.1016/s1413-8670(11)70229-x
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus detection and typing using a nested-PCR-RFLP assay

Abstract: The method of nested-PCR proved to be an effective diagnostic tool for HPV detection and typing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 28 publications
0
15
0
1
Order By: Relevance
“…The high prevalence of oncogenic genotypes found in this study indicates the need for frequent monitoring, and suggests nPCR technique for DNA-HPV detection as an alternative to early identification of women at high risk for cervical cancer development. Previous studies have already demonstrated that the use of primers pair MY09/11 and GP5/GP6 in a nPCR assay increases the sensitivity of HPV detection compared with PCR assay (Seaman et al , 2010; Coser et al , 2011). …”
Section: Discussionmentioning
confidence: 99%
“…The high prevalence of oncogenic genotypes found in this study indicates the need for frequent monitoring, and suggests nPCR technique for DNA-HPV detection as an alternative to early identification of women at high risk for cervical cancer development. Previous studies have already demonstrated that the use of primers pair MY09/11 and GP5/GP6 in a nPCR assay increases the sensitivity of HPV detection compared with PCR assay (Seaman et al , 2010; Coser et al , 2011). …”
Section: Discussionmentioning
confidence: 99%
“…HPV DNA samples were analyzed by first applying SB01/02 PCR primers ( Table 1 ) according to Coser et al [ 29 ] To increase the HPV detection rate the assay was modified and optimized for template concentration (3 μl in a final volume of 20 μl reaction), annealing temperature (42 °C), duration of each step (as indicated in Table 2 ), number of cycles (from 20 to 40 in two steps), and the MgCl 2 concentration that was adjusted to 3.5 mM. Thermal cycling conditions for outer PCR ( Table 2 ) were modified from Coser et al [ 29 ]. PCR product was approximately 495 bp for the majority of HPV genotypes.…”
Section: Methodsmentioning
confidence: 99%
“…The primers target conserved regions of the HPV genome, such as the L1 capsid gene [37]. After amplification, the HPV genotypes can be determined separately, using techniques such as restriction-fragment length polymorphism (RFLP), linear probe assays, direct sequencing, or genotype-specific primers [38]. Some researchers have used a type-specific PCR, with primers that amplify the long control region L1 and E6/E7 [39].…”
Section: Introductionmentioning
confidence: 99%
“…Amplification of samples containing DNA from more than one HPV genotype can lead to a much stronger amplification of one of the sequences present, which would complicate the detection of all genotypes in a sample with multiple infections. Sometimes, additional, labor-intensive procedures, such as sequencing or type-specific PCR, are required [38]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation